Antileishmanial activity of a new chloroquine analog in an animal model of Leishmania panamensis infection. (December 2020) - Herrera, Lizzi; Llanes, Alejandro; Álvarez, Jennifer; Degracia, Kissy; Restrepo, Carlos M.; Rivera, Rene; Stephens, David E.; Dang, Hang T.; Larionov, Oleg V.; Lleonart, Ricardo; Fernández, Patricia L.
Abstract: Leishmania panamensis is a relevant causative agent of tegumentary leishmaniasis in several Latin American countries. Available antileishmanial drugs have several limitations including relatively high toxicity, difficult administration, high production costs and the emergence of resistance in circulating strains. Therefore, the identification of new molecules as potential therapeutics for leishmaniasis is of great relevance. Here, we developed a murine model of L. panamensis infection and evaluated the effect of a new compound in vivo . After treatment of animals with the compound, we observed a significant reduction of inflammation and parasite load at the inoculation site, in a dose-dependent manner. We observed a reduction in IL-10 production by popliteal lymph nodes cells of infected mice. These results pave the way for future evaluation of this compound as a potential antileishmanial drug or as a suitable scaffold for lead optimization strategies. Graphical abstract: Image 1